PENINGKATAN PERILAKU IBU DALAM PENGATURAN POLA MAKAN BALITA DI POSYANDU MELATI DESA BINTORO KECAMATAN PATRANG KABUPATEN JEMBER - Asih*, Susi Wahyuning (The Indonesian Journal of Health Science, 2016)
The improvement of mother behavior in order to set toddler?s eating pattern in Bintoro village Patrang subdistrict of Jember is based on consequenses of the growth and developmental proccess of toddler itself. The purpose of this study is to find out mother?s behavior improvement. It?s a correlational study conducted by cross sectional approach. The population are 139 toddler?s mother in bintoro. There were 103 respondents taken y random sampling. The instruments was a questionnaire and WHO chart. The data analysed by using Spearman Rank test. The result shows that 51 respondents are showing not good while 42 respondents had their toddler with good nutritional status. The correlational analysis obtained p value 0.21 means that there is no significant correlation between mother?s behavior about diet with nutritional status of children under five in Bintoro village Patrang subdistrict of Jember. Keywords : mother behavior,nutritional status, children  under five